Sobre a filosofia social de Alfred Schütz: o começo de seu pensamento (Phenomenology, Humanities and Sciences, 2024)
From the reading of the work of Alfred Schütz, the present work aims to explore the beginning of his social philosophy. To this end, a brief overview of Schütz's life is presented, as well as the context in which his writings are inserted. As a milestone in the beginning of Schütz's thought, the text presents the work Fenomenología del mundo social (Der sinnhafte Aufbau der sozialen Welt, originally published in 1932). The book is built from the dialogue between Max Weber's comprehensive sociology, more specifically his theory of social action, and the philosophies of Henri Bergson and Edmund Husserl. Schütz (1972) starts from a critique of the lack of philosophical support of some of Weber's concepts and seeks such support in Bergson and Husserl. From this initial proposal, Schütz constitutes an original possibility of reading the world.
Keywords: Alfred Schütz; Phenomenology; Philosophy; Sociology